How Much Would Bangladesh Gain from the Removal of Subsidies on Electricity and Natural Gas? - Timilsina, Govinda R. (World Bank, Washington, DC, 2018)
As in many countries around the world, subsidies to energy in Bangladesh impose a significant fiscal burden, with benefits that disproportionately accrue to high-income households. Any reforms of energy subsidies should benefit the overall economy rather than those who use energy the most. Using a computable general equilibrium model, this study investigates the economywide impacts of the removal of direct subsidies in the electricity sector and indirect subsidies in natural gas in Bangladesh. The study finds that removal of energy subsidies would be beneficial to the economy and would increase gross domestic product. The magnitude of the economic impact depends on how the budgetary savings from the removal of the electricity subsidies and increased revenues due to the removal of indirect subsidies to natural gas are reallocated to the economy. Recycling the savings (or the new revenues) to fund investment would benefit the country most, followed by the case of utilizing them to fund cuts in income taxes, and finally to fund cuts in indirect taxes. Although the reallocation of budgetary savings to households through lump-sum transfers is found to be inferior to the other recycling options considered, it would be the preferred option from the distributional perspective.